The Psychosocial Determinants of Obesity Associated with Food Intake (Narrative Review) - Salma Mahmoodianfard; Neda Haghighat (Shiraz University of Medical Sciences, 2023)
Obesity is known as a major public health problem, with multi-factorial aspects. A complex interaction among genetic, physiological, and behavioral variables affects both the development and maintenance of the obese condition. Currently, there is an increasing interest in recognizing the significant role of psychosocial determinants of dietary behaviors to develop effective interventional weight loss programs. A review of the existing knowledge about the psychosocial determinants of food intake may be beneficial for developing dietary behaviors for health promotion among the populations. Differences in the psychosocial determinants of eating between obese and nonobese individuals and youth and adult groups provide a better understanding of the drivers of socioeconomic disparities in dietary intake, and how to develop targeted intervention strategies. In this review, we discussed the basic psychosocial concepts and theories related to food behaviors. Then, the psychological factors associated with the obesity-related food behaviors and the comparisons between the correlates of dietary behavior in obese and non-obese individuals were explained. Finally, the results of population-based studies which have addressed the contribution of dietary behavior among the youth and adults were presented.